2015
DOI: 10.7314/apjcp.2015.16.11.4477
|View full text |Cite
|
Sign up to set email alerts
|

'Drawing' a Molecular Portrait of CIN and Cervical Cancer: a Review of Genome-Wide Molecular Profiling Data

Abstract: tumor formation and growth is continuous mutagenesis, microevolution and changes in the tissue microenvironment, its molecular-genetic 'portrait' is dynamic and tightly bound to the stage of the disease.Cervical cancer (CeCa) is an example of oncopathology, for which the whole continuum of carcinogenesis, from the earliest stages-cervical intraepithelial neoplasia (CIN) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…A previous study revealed that cervical lesion is an infectious disease caused by HPV [1]. Persistent high-risk HPV infection is a major risk factor to induce cervical lesions and promote its progression [6]. However, the vast majority of HPV infections and CIN I, half of CIN II, and 30% of CIN III cases, can be spontaneously reversed [7], which ultimately does not cause cervical cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that cervical lesion is an infectious disease caused by HPV [1]. Persistent high-risk HPV infection is a major risk factor to induce cervical lesions and promote its progression [6]. However, the vast majority of HPV infections and CIN I, half of CIN II, and 30% of CIN III cases, can be spontaneously reversed [7], which ultimately does not cause cervical cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…Uprising research on cancer has defined the genetic and epigenetic basis as fundamental but complex phenomenon that interacts during the development and progression of malignant cells into invasive tumors. 43 Though numerous population based studies have been performed but due to poorly understood biology, multiple risk factors, 44 molecular abnormalities, 45 as well as genetic diversity necessitated continuous investigation of novel targets in cervical carcinogenesis. This study, therefore, aimed at determining the contribution of genetic and epigenetic aberrations among novel and critical tumor suppressor component (genes), such as PARK-2 linking it not only with cervical carcinogenesis but their association with pathological markers which could be a promising approach in combating the fatal disease in future.…”
Section: Discussionmentioning
confidence: 99%
“…Each molecular profile (genome, transcriptome, proteome, etc.) in the dynamics of the development of the disease progression gradually accumulates multiple aberrations and thus contributes to the development of the tumor [81]. Despite the large number of publications dedicated to various aspects of cervical carcinogenesis, pathologists still play an important role in the development of diagnostic approaches and targeted therapies aimed at tumors characterized by a certain phenotype and the presence of biomarkers that allow the response to targeted therapy to be predicted, enabling the monitoring of response to treatment [92].…”
Section: Vaginal Microbiome Inflammation and Immune Homeostasismentioning
confidence: 99%